Clinical case of combined correction of children's psychotraumatic experience and distress in the development of cancer - K. A. Blinova; E. V. Pchelintseva; N. P. Lapochkina (Исследования и практика в медицине, 2020)
The article describes the results of applying the combined correction of the consequences of childhood traumatic experience, which served as the trigger that launched the onset of cancer distress. A patient with oncopathology (breast cancer) had signs of a sensitive, anxious-phobic personality. In the absence of the ability to cope with children's fears, a distress associatively occurs – a negative emotional state that did not allow finding a way out of the created conditions. The main prerequisite for the development of distress can be considered children's traumatic experience gained in the early stages of ontogenesis, amplified by negative memories of the loss of parents, loss of moral support for loved ones; the formation of a chronic state of loneliness, continuous anxiety regarding personality changes, depressed mood and mental activity. The clinical example described in the article illustrates the close pathological relationship of childhood traumatic experience and the occurrence of the disease, and also confirms the presence of a nonspecific psychosomatic disease in the framework of the diathesis-stress model. The psychological rehabilitation of the patient included the initiation of post-traumatic growth, self-knowledge, development of stress tolerance, activation of creative potential, finding a life goal, and finding harmonious interpersonal relationships. It is shown that the psychotherapeutic techniques used in the framework of the adapted diathesis-stress model (psychosynthesis, short-term analytical psychodrama, cognitive-behavioral psychotherapy) allow us to determine a behavior strategy in overcoming the traumatic situation that occurred in the early stages of childhood, in order to form the skills of the correct expression of our emotions, avoiding this deconstructive "coping" – strategy.